Integrasi Kearifan Lokal dan Hukum Positif dalam Pengelolaan Lingkungan - Salamena, Hanny Jermias Onisimus; Saleh, Moh. (Legal Standing : Jurnal Ilmu Hukum, 2025)
The practice of land clearing by burning forests has long been a part of indigenous communities' local wisdom in North Sumatra to enhance soil fertility. However, this practice conflicts with Indonesia’s positive laws, particularly Forestry Law No. 41 of 1999 and Environmental Protection Law No. 32 of 2009. This study aims to analyze the integration of local wisdom and positive law in environmental management. Using a qualitative approach with a case study method, the research examines the case of Sorbatua Siallagan, where land clearing in protected forest areas led to legal consequences. The findings reveal that while indigenous practices contribute to sustainable land use, they also pose environmental risks, including forest fires and air pollution. Therefore, strengthening dialogue and empowering indigenous communities with environmentally friendly agricultural techniques is necessary to harmonize local traditions with legal regulations, ensuring environmental sustainability and community welfare.